1993
DOI: 10.1017/s0950268800057228
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and clonal relationships ofAcinetobacter baumanniistrains isolated in a neonatal ward: epidemiological investigations by allozyme, whole-cell protein and antibiotic resistance analysis

Abstract: SUMMARYSixty-five strains of Acinetobacter baumannii which had been isolated from patients and the indoor environment of a neonatal intensive care unit and, for comparative purposes, isolates from three other wards, were examined by means of electrotyping and analysis of whole-cell protein and antibiotic resistance patterns. Fourteen different electrotypes were determined. The predominant type, a multiply resistant acinetobacter clone, persisted in the neonatal ward over several months. The results underline t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Investigation of 27 esterases and 2 dehydrogenases in 81 Acinetobacter isolates identified between 2 and 17 variants for each enzyme (150). A separate study of 13 enzymes in 65 Acinetobacter clinical isolates identified 14 different types, of which 1 type was found in 41 multiresistant isolates with common whole-cell protein profiles (193). These results suggest that multilocus enzyme electrophoresis has the potential to be developed into a useful technique for strain identification.…”
Section: Multilocus Enzyme Electrophoretic Typingmentioning
confidence: 86%
“…Investigation of 27 esterases and 2 dehydrogenases in 81 Acinetobacter isolates identified between 2 and 17 variants for each enzyme (150). A separate study of 13 enzymes in 65 Acinetobacter clinical isolates identified 14 different types, of which 1 type was found in 41 multiresistant isolates with common whole-cell protein profiles (193). These results suggest that multilocus enzyme electrophoresis has the potential to be developed into a useful technique for strain identification.…”
Section: Multilocus Enzyme Electrophoretic Typingmentioning
confidence: 86%
“…Other researchers compared protein typing by SDS‐PAGE and allotyping for selected bacterial enzymes as a means to track isolates in epidemiological investigations. Although allotyping had the greatest discriminating power, protein analysis was concluded to be more widely applicable between diverse bacterial systems 24, 25. Not all of the comparative studies of the protein profiles used detailed cluster analysis for their comparisons and manual comparisons were still widely used 24.…”
Section: Typing Bacteria Using 1‐d Sds‐pagementioning
confidence: 99%
“…For several years, the prevalence of infection with MDR A. baumannii has been increasing dramatically in the European countries that is, from 15.4% in 2004 to 48.5% in 2014 [8]. In the late 20th century, A. baumannii has emerged as a significant nosocomial pathogen in Germany [9][10][11]. Numerous nosocomial outbreaks were reported among inpatients and preterm infants with a considerable mortality rate of up to 24% after bacteremia in intensive care units at a large teaching hospital of Cologne [12].…”
Section: Introductionmentioning
confidence: 99%